2005
DOI: 10.1098/rspb.2004.2968
|View full text |Cite
|
Sign up to set email alerts
|

Aposematism: what should our starting point be?

Abstract: The evolution of aposematism is considered to be a major evolutionary problem because if new aposematic forms emerged in defended cryptic populations, they would face the dual problems of rarity and conspicuousness. We argue that this commonly assumed starting point might not have wide validity. We describe a novel evolutionary computer model in which prey evolve secondary defences and become conspicuous by moving widely over a visually heterogeneous habitat. Unless crypsis imposes high opportunity costs (for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 47 publications
3
63
1
Order By: Relevance
“…These findings support theories of aposematism acting as a honest handicap signal [27]. Paradoxically, other theories predict negative correlation when well defended prey are able to avoid predation and can therefore reduce costs incurring by signalling [1,13,14,28]. Therefore, no consistent explanation of the relation between aposematic display and levels of secondary defence exists.…”
Section: Introductioncontrasting
confidence: 33%
See 1 more Smart Citation
“…These findings support theories of aposematism acting as a honest handicap signal [27]. Paradoxically, other theories predict negative correlation when well defended prey are able to avoid predation and can therefore reduce costs incurring by signalling [1,13,14,28]. Therefore, no consistent explanation of the relation between aposematic display and levels of secondary defence exists.…”
Section: Introductioncontrasting
confidence: 33%
“…This seems like a reasonable conclusion and for questions related to the possibility of overcoming the stability of crypsis this paper refers to models of the initial emergence of aposematism describing mechanisms such as dietary conservatism, a shifted peak of the aversive information function, the opportunity cost of crypsis, and specific properties of the predator's perception or cognitive processes [13,17,18,28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work suggested that aposematic coloration releases prey species to explore more environmental opportunities than a cryptic phenotype because an aposematic signaler is no longer constrained to a particular visual background (13,47). However, aposematism in Papilio larvae has had the opposite effect, meaning that aposematic lineages are constrained to particular host plant growth forms, specifically narrow-leaved herbs and shrubs.…”
Section: Discussionmentioning
confidence: 91%
“…An organism is defined as aposematic when it possesses both a defensive trait that makes it unpalatable and a warning signal to advertise its defense to potential predators (Poulton 1890;Ruxton et al 2004;Mappes et al 2005). The initial evolution of aposematism is often considered paradoxical because of the predicted higher predation costs associated with the original appearance of conspicuousness, which may not yet be associated with a defense (Lindström et al 2001;Ruxton et al 2004;Speed and Ruxton 2005). In general, predators learn to avoid aposematic prey more quickly when the diversity of warning signals is low, compared to higher signal diversity (Joron and Mallet 1998;Rowland et al 2007).…”
Section: Introductionmentioning
confidence: 99%